Marketing social change : - Andreasen, Alan R (Jossey-Bass, 1995)
Thsi important book offers a revolutionary approach to solving a range of social problems--drug use, smoking, unsafe sex, and overpopulation--by applying marketing techniques and concepts to change behavior. For example, it shows that at-risk teenagers are consumers who decide whether or not to ``buy'' safe sex practices. This successful approach is based on Alan R. Andreasen's more than twenty years' experience of consulting, teaching, and research with social marketing programs around the world.